Domestic Violence among Ever Married Women of Reproductive Age Group in a Rural Area of Karnataka: A Cross Sectional Study - Ramaiah, Radha; Jayarama, Srividya (National Journal of Community Medicine, 2017)
Background: Domestic violence is a widespread social evil and continues to be a major public health problem. Domestic violence by marital partners is the most common type of violence against women. This not only has serious impact on their physical, mental health but also impedes women’s socio-economic development. Objectives: 1. To determine the prevalence of domestic violence among the ever married women in reproductive age group. 2. To identify the types of domestic violence and factors associated with it. Methodology: A Community based, cross sectional study was conducted in Javarnahalli, a rural field practice area of AIMS, BG Nagara, Mandya. Study population constituted all 186 married women of reproductive age group (15-49 years) residing in Javarnahalli. Ethical committee approval, informed consent from study participants was taken. A pre designed, pretested structured questionnaire was used for data collection. Statistical analysis was done using SPSS version 20. Results: The overall prevalence of domestic violence was 54.3%. 42.1% suffered from both current and lifetime physical and psychological violence. 48% suffered from both current and sexual violence. Conclusion: In this context, more social support for women, community awareness, making women self reliant by increasing their literacy levels can be recommended.